SMN is required for dynamic relocalization of methylated nucleolar proteins during skeletal muscle differentiation - Paquette, Benoit F (University of Ottawa (Canada), 2008)
Deletions or loss-of-function mutations in the Survival of Motor Neuron 1 (Smn1) gene in humans is responsible for Spinal Muscular Atrophy (SMA), one of the leading genetic causes of infant mortality. The pathological hallmarks of this disease include the degeneration of lower motor neurons in the anterior horn of the spinal cord, weakness, paralysis and atrophy of the associated skeletal muscles and eventually of the entire trunk, often times causing respiratory failure and early death during disease progression. Although current knowledge supports the notion that this disease arises from the massive motoneuron loss early in development, mounting evidence suggests that intrinsic muscle defects may also contribute to the pathology. Arginine methylation is also known to be important for normal skeletal muscle differentiation. Since SMN can serve as an adaptor module for arginine methylated proteins, we speculated that SMN will perform its function in skeletal muscle by promoting methyl-dependent interactions. This study has documented a dynamic profile of proteins containing methylated arginines during myoblast differentiation, and that this dynamic profile is dependent on the presence of SMN. Furthermore, I have identified Fibrillarin, a snoRNP component, as one of the methylated proteins that is misregulated in the absence of SMN. Finally, I have also shown that the profile of arginine methylated proteins differs between skeletal muscles from wild type mice and a mouse model of SMA. Taken together, these results represent a novel defect in SMA and provide evidence for the importance of skeletal muscle tissue in this disease.
Keywords: Biology, Molecular.; Biology, Cell.